2014
DOI: 10.4236/abc.2014.44030
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antibacterial Activity of Essential Oils from <i>Struchium sparganophora</i> Linn. Ktze Asteraceae

Abstract: Struchium sparganophora Linn. Ktze Asteraceae is a culinary herb that is consumed in the Western part of Nigeria and has wide medicinal uses in traditional medicine. The present study was carried out to determine the chemical composition of the oils from its leaf and stem and their antibacterial activity. Essential oils were collected from the leaf and stem of Struchium sparganophora by hydrodistillation and analysed by GC and GC-MS. The antimicrobial activity was tested against Gram negative (G − ve) and Gram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Although the essential oil of Mentha suaveolens showed strong antibacterial activity against S. xylosus with an MIC value of 14.4  μ L/mL, it showed no activity against lactic acid bacterial strains except Lactococcus lactis [41]. The essential oil of the herb Struchium sparganophora revealed the presence of β -caryophyllene, germacrene A, α -humulene, and germacrene D as major chemical constituents and it exhibited antibacterial activity against S. typhi, B. cereus, B. subtilis, P. mirabilis, and P. aeruginosa [72]. The inhibitory zone for leaf oil ranged from 9.0 ± 1.0 to 14.3 ± 2.55 mm, whereas the essential oil from stem had inhibitory activity ranging from 18.5 ± 2.2 to 20.0 ± 0.0 mm.…”
Section: Antimicrobial Effects Of Essential Oilsmentioning
confidence: 99%
“…Although the essential oil of Mentha suaveolens showed strong antibacterial activity against S. xylosus with an MIC value of 14.4  μ L/mL, it showed no activity against lactic acid bacterial strains except Lactococcus lactis [41]. The essential oil of the herb Struchium sparganophora revealed the presence of β -caryophyllene, germacrene A, α -humulene, and germacrene D as major chemical constituents and it exhibited antibacterial activity against S. typhi, B. cereus, B. subtilis, P. mirabilis, and P. aeruginosa [72]. The inhibitory zone for leaf oil ranged from 9.0 ± 1.0 to 14.3 ± 2.55 mm, whereas the essential oil from stem had inhibitory activity ranging from 18.5 ± 2.2 to 20.0 ± 0.0 mm.…”
Section: Antimicrobial Effects Of Essential Oilsmentioning
confidence: 99%
“…Cl-EO and Cm-EO showed its potential to inhibit the growth of human pathogenic organism by showing highest activity in P. aerogenosa. Similarly, oils from A. clavennae (Skočibušić et al, 2004), S. sclarea (Cui et al, 2015), Satureja cuneifolia (Oke et al, 2009), Salvia lavandulifolia (Jirovetz et al, 2007), Struchium sparganophora (Kasim et al, 2014), Syzygium cumini (Mohamed et al, 2013) showed inhibitory effect against P. aeruginosa.…”
Section: Resultsmentioning
confidence: 96%